The spatial thinking process of the field-dependent students in reconstructing the geometrical concept - Henry Suryo Bintoro; Yohanes Leonardus Sukestiyarno; Mulyono Mulyono; Walid Walid (Institute of Advanced Engineering and Science, 2022)
Reconstructing geometrical concepts requires a spatial thinking process, so the spatial thinking process will be correct and complete. The phenomena of cognitive style differences cause different perceptions and thinking activities to solve geometric problems. This qualitative-explorative research describes the spatial thinking process of students with field-dependent cognitive styles in reconstructing the concept of spatial geometry based on the theory of Action-Process-Object-Schema (APOS). The research subjects were 27 students and obtained five students with field-dependent cognitive styles. The researchers used a purposive sampling technique from the subjects with a certain consideration. The researchers selected a student that met the three elements of spatial thinking and the five indicators of spatial ability. This research collected the data with interviews, documentation, and group embedded figure test (GEFT). The analyzing techniques used data collection, data reduction, data presentation, and concluding. The spatial thinking process of the field-dependent students had a spatial category with three indications: i) Inaccuracy in the elements of representational thinking; ii) The inaccuracy of spatial perception indicators; and iii) Not using de-encapsulation mental mechanisms.